Trends in the quality & quantity of otorhinolaryngology research in Australia: 1989–2018 - Bell-Allen, Nicholas; Cervin, Anders; Vasani, Sarju (Australian Journal of Otolaryngology; Vol 2 (April 2019): Australian Journal of Otolaryngology, 2019)
Background: Trends in the quality and quantity of surgical research in Australia have recently experienced considerable growth, stemming from the adoption of the “evidence-based practise” framework. The aim of this 30-year retrospective epidemiological study is to identify and analyse trends in publication of clinical otorhinolaryngology research in Australia from 1989 to 2018. Methods: The 24 highest ranked otorhinolaryngology journals worldwide were identified based on their respective impact factor (IF). Using OVID MEDLINE/PubMed, each Journal was searched for publications with an Australian affiliation for the last 30 years. One investigator screened and analysed results, collecting relevant data for all articles meeting inclusion criteria. Results: A total of 1,095 articles were identified from the period between 1989–2018. There has been an exponential increase in the total number of publications throughout this time. Randomised controlled trials (RCTs) accounted for 36 publications, whilst systematic reviews were tallied at 53 publications; with a trend towards publication of higher (level 1 & 2) levels of evidence. Level 4 evidence (prospective or retrospective case series), accounted for the largest quota of study designs, at 535 articles (48.9%). Furthermore, there has been a statistically significant increase in both multi-institutional and multinational collaborative research. Conclusions: There has been a considerable increase in the quantity and quality of otorhinolaryngology research within Australia in the last three decades. This is largely due to a strong impetus from the Royal Australasian College of Surgeon (RACS) on a developing academic surgical culture in concordance with financial support from bequeathing otorhinolaryngology foundations and a trend towards more multi-institutional and multinational collaboration.